Alphabet Flashcards: Instructional Media in the Process of Learning While Playing at the Community Learning Activity Center - Mozes Markus Wullur; Marien Pinontoan; Ronny G. Dumanaw; Abdul Rahmat (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purposes of this research are to design, apply, and find the effectiveness of alphabet card learning media in the Community Learning Activity Center (hereafter, PKBM) in North Sulawesi Province. This study used the Research and Development method, following the stages of ADDIE model development research. This research is designed for 2 years and the first year 2022 has been carried out in 3 stages, namely: 1) Analyze stage, 2) the Design stage, and 3) the Development Stage. Meanwhile, for the second year, there will be 2 stages, the Implementation Stage, and the Evaluation stage. It was concluded that the prototype product design of Alphabet Card Learning The application of the development of the learning process is carried out through stages: recruitment of tutors, learning residents and forming study groups, conducting Training of Trainers (TOT) for tutors; and trials development. The learning process is effective because the residents who were formerly literate but forgot their letters have re-learned them, an improvement in the cognitive abilities to learn citizens, a better ability to put letters together to form meaningful words, and citizens who are learning become more involved. It is suggested that: 1) The teacher must develop an adaptable lesson plan; 2) The following aspects require revision: (1). the physical card alphabet's size in both height and width; (2). For the sake of IPR and patent rights, a unique logo is required. 3). At the Implementation and Evaluation stage, this study must be continued.